Decision Making on Breakwater Type Selection on Tidung Island, Thousand Islands - Bram Soepradono; Endah Kurniyaningrum (Pandawan Sejahtera Indonesia, 2026)
Tidung Island, a major tourist destination in the Thousand Islands, faces coastal erosion caused by wave energy, tidal currents, and anthropogenic activities, which threaten coastal ecosystems, marine tourism quality, and residential areas. Coastal protection measures have been implemented through wave protection structures. However, their performance has been suboptimal due to limited maintenance, design incompatibility with local hydro-oceanographic conditions, and the absence of a systematic approach for selecting breakwater types. This study aims to identify the criteria and sub-criteria influencing breakwater selection and determine the most suitable structure for Tidung Island using the Analytic Hierarchy Process (AHP). The AHP model integrates technical, environmental, socio-economic, field condition, and construction method aspects, based on secondary hydro-oceanographic data (tides, wind, wave height, and effective fetch) and expert judgments through pairwise comparisons. The results show that technical aspects have the highest priority (0.312), followed by environmental aspects (0.268), field conditions (0.201), socio-economic factors (0.127), and implementation methods (0.092), with all consistency ratio values below 0.10. The selected structure is a hollow cube breakwater with a filter-coated rockfill foundation, as it provides an optimal balance between technical performance, cost efficiency, ease of implementation in shallow waters, and manageable environmental impacts. This AHP-based model can support sustainable coastal protection decision-making.